Late oligocene to quaternary tectonic evolution of the extra andean basins of the pampean plain, Argentina. (October 2019) - Folguera, Alicia; Zárate, Marcelo
Abstract: The extra-Andean Pampean plain of central Argentina shows a complex evolution history. Three basins were identified in the subsurface (Salado, Macachín and Laboulaye) generated during the opening of the South Atlantic Ocean in the Mesozoic with a continuous subsidence history from the Oligocene to the Quaternary. The purpose of this contribution is to analyze the Cenozoic sedimentary filling of the Pampean plain basins with the goal of interpreting the tectonic evolution and understand the subsidence history. The study was based on the correlation and integration of subsurface data. Isopach maps were constructed from boreholes logs for each stratigraphic unit to infer depositional patterns, temporal and spatial thickness distributions, and possible depocenter migrations. The data was integrated in order to analyze the subsidence history of the basins and evaluate the potential mechanisms of post-rift tectonic reactivation of the passive margin. The Cenozoic sedimentary record was divided into three intervals for purposes of analysis with contrasting distribution and mechanisms. The late Oligocene-early Miocene (∼27-19 My) interval started before and continued during the earliest stage of the Andean orogeny; the second interval (early Miocene-middle Miocene 19-15 My) that coexisted with the initial stages of Andean uplift and the third interval (middle Miocene-Quaternary, 15 My-Quaternary) developed during the last stages of the Andean orogeny. The subsidence during the late Oligocene-early Miocene was geographically restricted to the pre-existent basins, so an extensional reactivation of the Mesozoic depocenters is proposed. It is considered to be associated with an Oligocene generalized extension responsible for basin development before the beginning of the Andean orogeny, which later shifted into transpressional conditions. The early Miocene sedimentation (19-15 My) is here interpreted as the result of subsidence during the beginning of the Andean orogeny due to a less common but lengthy process that may lead to foreland rifting or transtension in the three analyzed basins. The middle Miocene-Quaternary (15 My-Present) interval is characterized by a blanket-like subsidence resulting in monotonous thicknesses with reduced-scale accumulation, both in the basins and over the relative highs. This sedimentation is interpreted as the result of accumulation in an extensive distal foreland basin with the foredeep located in the Alvear basin, the forebulge in the Pampa Central block, and the backbulge in the Laboulaye, Macachín and Salado basins. Located far east from the Andean tectonic loads, this distal foreland basin cannot be solely explained by short-wave subsidence patterns. Thus, dynamic subsidence is here proposed as an additional mechanism. Highlights: Three basins were identified in the subsurface with a continuous subsidence history from the Oligocene to the Quaternary. The purpose is to analyze the Cenozoic sedimentary filling of the Pampean plain basins based on subsurface data. Isopach maps were constructed from boreholes logs for each stratigraphic unit. The Cenozoic sedimentary record was divided into three intervals for purposes of analysis. This distal foreland basin cannot be explained by short-wave subsidence patterns. Dynamic subsidence is here proposed as an additional mechanism.